FORWARD-LOOKING INFORMATION DISCLOSURE AND FIRM VALUE IN THE PANDEMIC ERA - Harjanti Widiastuti; Evy Rahman Utami; Erna Purnamasari (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
The study investigates the forward-looking information disclosure (FLID), firm performance, and firm value during the COVID-19 pandemic. The population of this study was firms listed on the Indonesia Stock Exchange (IDX). The sampling methods used purposive sampling based on specific criteria. Our total sample was 478 observations. The data were analyzed based on multiple regressions utilizing the EViews program. The results of this study revealed that forward-looking information disclosure did not affect firm value. However, firm performance has a positive effect on firm value. Therefore, the interaction of firm performance and forwardlooking information positively affects firm value. During the pandemic, managers disclose more forward-looking information than before the pandemic.